Computed Tomography-Derived Transesophageal Echocardiographic Views: Step Forward for Procedural Planning of Transcatheter Tricuspid Valve Annuloplasty. (January 2021) - Fortuni, Federico; Hirasawa, Kensuke; Marques, Ana I.; Pio, Stephan M.; Chimed, Surenjav; Lustosa, Rodolfo; Tjahjadi, Catherina; Wang, Xu; Bax, Jeroen J.; Ajmone Marsan, Nina; Delgado, Victoria
Abstract : Supplemental Digital Content is available in the text.